Stability analysis and numerical simulation of foundation in old goaf under building load - Zhang, Xiangdong; Li, Wenliang; Li, Tianyu; Li, Zong; Cai, Guanjun; Shen, Zhen; Li, Rantong (Frontiers in Earth Science, 2023)
This study comprehensively analyzes the safety and stability of old goaf under construction engineering based on specific projects using a variety of research methods. The Beijing Mentougou mining area is used as the research background. The methods of field investigation, laboratory testing, engineering drilling, geophysical exploration, theoretical calculation, and numerical simulation are combined to quantitatively analyze the stability of the foundation and ground buildings in old goaf. The influence depth of the building load and height of the caving crack zone are calculated using the “three-zone theory” to judge if the goaf is at risk of activation. Further simulation is conducted using two types of finite element analysis software, which increases the reliability of the numerical analysis. The results demonstrate that uneven subsidence of approximately 100 mm occurs in the buildings and ground surface, and subsidence of approximately 50 mm occurs in the goaf roof. It is also proven that goaf affects the stability of the surrounding rock and building foundation. Finally, a goaf treatment scheme is proposed. The treatment effect is found to be remarkable through field tests and numerical simulations, ensuring the safety and stability of a building foundation. The combination of theoretical calculation and numerical simulation can effectively evaluate the safety and stability of the project under load, and has a strong promotion and application value. The research results meet the needs of engineering practice, and provide a great reference value for the rational utilization of the land above the old goaf in the Mentougou district of Beijing and similar mining cities, which has a good theoretical significance and application prospect.